The role of management’s perceived usefulness of accounting information in enhancing accounting information quality: The mediating effects of accounting information system quality and accounting staff competence - Phan, Hoang-Long; Huynh, Hong-Hạnh Thị (Asian Economic and Financial Review, 2025)
This study investigates how management’s perceived usefulness of accounting information influences the quality of accounting information, with a particular focus on the mediating roles of accounting information processing system quality and accounting staff competence. Data were collected through a structured survey of 212 firm executives and accounting managers in Vietnam. The study employed exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and structural equation modeling (SEM) to validate the measurement model and test the hypothesized relationships. The results confirm that management’s perception of the usefulness of accounting information directly enhances the quality of accounting information. It also indirectly improves accounting information quality by enhancing the accounting information system and the competence of accounting staff. These mediators account for 54.2% of the total effect, highlighting their critical roles in translating management’s perception into tangible improvements in accounting information quality. Our findings provide practical insights for policymakers and business leaders, especially in developing economies where integrating accounting information systems and developing accounting personnel remain challenging.